Per Olof Berg, Anders Linde-Laursen & Orvar Löfgren (eds.): Invoking a Transnational Metropolis. The Making of the Øresund Region - Olwig, Kenneth R. (Tidsskriftet Antropologi, 2002)
Anmeldes af Kenneth R. Olwig